Towards Control of the Size, Composition and Surface Area of NiO Nanostructures by Sn Doping - Taeño, María (Nanomaterials (Basel), 2021)
Achieving nanostructures with high surface area is one of the most challenging tasks as this metric usually plays a key role in technological applications, such as energy storage, gas sensing or photocatalysis, fields in which NiO is gaining increasing attention recently. Furthermore, the advent of modern NiO-based devices can take advantage of a deeper knowledge of the doping process in NiO, and the fabrication of p-n heterojunctions. By controlling experimental conditions such as dopant concentration, reaction time, temperature or pH, NiO morphology and doping mechanisms can be modulated. In this work, undoped and Sn doped nanoparticles and NiO/SnO(2) nanostructures with high surface areas were obtained as a result of Sn incorporation. We demonstrate that Sn incorporation leads to the formation of nanosticks morphology, not previously observed for undoped NiO, promoting p-n heterostructures. Consequently, a surface area value around 340 m(2)/g was obtained for NiO nanoparticles with 4.7 at.% of Sn, which is nearly nine times higher than that of undoped NiO. The presence of Sn with different oxidation states and variable Ni(3+)/Ni(2+) ratio as a function of the Sn content were also verified by XPS, suggesting a combination of two charge compensation mechanisms (electronic and ionic) for the substitution of Ni(2+) by Sn(4+). These results make Sn doped NiO nanostructures a potential candidate for a high number of technological applications, in which implementations can be achieved in the form of NiO–SnO(2) p-n heterostructures.